A Prototype of Phase Lock Loop System on Communication Device for Motorcycle Riders - admin admin (Journal of Informatics and Communication Technology (JICT), 2019)
In recent years, technology has developed rapidly, particularly technology in The telecommunication sector. As the electronic sector has been developing, as well as the increasing number of motorcycle riders and its communities, the authors are interested in designing an assistive device for motorcycle drivers. This device is designed as an additional communication tool for the coordination between the drivers. For communication, it is necessary to create a communication system without interfering with other riders. Therefore, the authors are motivated to design " a prototype of a phase lock loop system on a communication device for motorcycle riders". Using radio frequency as a media, this device aid motorcycle riders to communicate with each other. In this research, the authors design and implement the prototype regarding its ability to receive communication through helmet having a lock loop phase system. The main aim of the research is creating a device that can be used as an alternative communication device for motorcycle riders which is economical and provide convenient communication and coordination between riders without causing any disturbances and hazards.